O Colombo que nasceu na América: figurações do self made man na literatura estadunidense – o romantismo de J. F. Cooper em Mercedes of Castile: or, the voyage to Cathay (1840) - BERNDT, JORGE ANTONIO (2022)
When the hypothesis that the interest of the human being for the past is considered, the study of the hybrid genres which mix history and fiction can contribute to the constitution of new perspectives. Such views could be related to events and characters whose depictions were established by the writing of the nationalist and romantic History. In this scenario, the historical novels which deal with the “Discovery of America” assume a special role in the formation of the continent, because it was this very moment that built the current identity (TODOROV, 1983). Included in the scope of the Research Group “Remeanings of the past in America: processes of reading, writing, and translating of hybrid genres of History and fiction – paths to decolonisation”, this dissertation analyses the novel Mercedes of Castile: or, the voyage to Cathay (1840), by James Fenimore Cooper. This is a novelistic report in which one of the most important socio-political events of Europe and America from the 15th century is told. The purpose is to demonstrate that Mercedes of Castile: or, the voyage to Cathay (COOPER, 1840) is an example of the modality of the Scottian classical historical novel, according to the assortment proposed by Fleck (2017) and to unfold how this form reverberated in the discursive construction of Christopher Columbus. To answer this problem, we compare the narrative structure and the writing strategies employed by its author with the characteristics of the Scottian canon present in Waverley ([1814], 1985) and Ivanhoe ([1819], 1994), written by Walter Scott – the initiator of the historical novel, in Lukács’ (2011) perspective. Concepts were taken from Comparative Literature and the field of studies dedicated to historical novel and its trajectory, with Lukács (2011), Aínsa (1988; 1991), Menton (1993), Hutcheon (1991), Mata Induráin (1995), Fernández Prieto (2003), Fleck (2007; 2010; 2014; 2017), among others. Through the analysis of such corpus, the first fictional images of the “Discovery of America” are revealed, as well as the inaugural fictionalisation of Christopher Columbus in prose, produced in the space of the United States from the 19th century. It aims to connect these first novelistic images of Cooper to the self-made man ideal. This approach further sought to clarify the historical and social aspects that led United States to become the home of the thematic of the “Discovery” within the trajectory of the novel, giving birth to the novelistic Columbus. Thus, with the proposed analyses, this text reveals how much Cooper’s writing is linked to the classical paradigms of the historical novel, consolidated by Walter Scott. As a result, it also stresses how the ideals of the United States’ romantic society are projected in the fictional images of Columbus, in order to shape a national identity, also through the literary art